DEVELOPMENT DEVELOPMENT OF E-MODULE ASSISTED BY BOOK CREATOR WITH 4D MODEL IN ICT PRACTICUM COURSE TO IMPROVE STUDENTS' LEARNING MOTIVATION - Deskoni; Dewi Koryati; Dewi Pratita; Resti Yunisetia; Imam Tantowi (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine the validity of the book creator-assisted e-module and to assess its effectiveness in enhancing students' learning motivation. This research was conducted using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate) for the 2021 economics education cohort, which consisted of 65 individuals as the research sample. Data was obtained through interviews and questionnaires. The research results show that the material validation is 86.88% and the media validation is 96%, categorized as suitable for use after revisions. The results from the questionnaire data indicate a significant effect on increasing learning motivation, where the t-test results show thitung ≥ ttabel, meaning that Ho is rejected and Ha is accepted. Additionally, there was an increase of 18.51% from the pre-test to the post-test, and the N-Gain result was 76.23%, categorized as effective. It can be concluded that the e-module assisted by Book Creator is suitable for implementation in learning activities based on the validation of materials and media. It is effective in enhancing students' learning motivation in the ICT practical course.